Interactive medical and safety monitoring in clinical trials with clinDataReview: a validated and open-source reporting tool - Cougnaud, Laure; Faes, Margaux; Van Krunckelsven, Dirk; De Roeck, Arne; Pasetto, Michela; Fieuw, Ann; Andersen, Claus A.; Meyvisch, Paul (Frontiers in Medicine, 2024)
Continuous medical and safety monitoring of subject data during a clinical trial is a critical part of evaluating the safety of trial participants and as such is governed by protocol procedures and regulatory guidelines to meet the trial's intended objectives. We present an open-source validated graphical tool (clinDataReview R package) which provides access to the trial data with drill-down to individual patient profiles. The tool incorporates functionalities that facilitate detection of error and data inconsistencies requiring follow-up. It supports regular medical monitoring and oversight as well as safety monitoring committees with interactive tables and listings alongside graphical visualizations of the primary safety data in reports. An implementation example is given where the tool is used to deliver validated outputs following FDA/EMA guidelines. As such, this tool enables a more efficient, interactive, and reproducible review of safety data collected during an ongoing clinical trial.